Risk factors for incident open-angle glaucoma: a population-based 20-year follow-up study - Ekström, Curt (Acta ophthalmologica (Oxford, England), 2012)
. Purpose:  To study the effect of potential risk factors on the development of open‐angle glaucoma (OAG) in a population in which pseudoexfoliation (PEX) is a common finding. Methods:  In 1984–1986, a population‐based survey of 760 people aged 65–74 years was conducted in the municipality of Tierp, Sweden. From 1988 to 2006, a follow‐up study of the 530 people with normal visual fields has been in progress. To increase the cohort, 273 ophthalmic outpatients were enroled. Reliable visual fields were available for 679 people, representing 6 126 person‐years at risk. A time‐weighted mean intraocular pressure (IOP) for all visits was calculated. Results:  Sixty‐four subjects developed definite OAG, 29 of whom were exposed to PEX. Risk factors associated with OAG were higher age, a positive family history, increased IOP and PEX. The age‐standardized rate ratio (SRR) was 14.8 times (95% confidence interval [CI] 7.92–27.8) greater in subjects with mean IOP ≥20 mmHg than in those with mean IOP <20 mmHg. When subjects with IOP <20 mmHg at baseline were affected by PEX, the SRR increased 5.01‐fold (95% CI 1.97–12.8), compared with the unaffected group. However, when mean IOP at follow‐up was taken into account, there was no relationship between OAG and PEX as a distinct risk factor. Among participants in the population survey, 69% of all cases were attributable to a mean IOP ≥20 mmHg. Conclusion:  Increased IOP and PEX were serious risk factors for incident OAG. The effect of PEX was mediated by increased IOP.